INTERVENCIÓN PÚBLICA EN LA EDUCACIÓN SUPERIOR - SUSANA FERNÁNDEZ ALFARO; SARA FERNÁNDEZ LÓPEZ (Revista Nacional de Administración, 2010)
Education is one of those public services that demandimportant resources from the State to guaranteeminimal quality standards. Therefore, governmentefforts have been focused on assessingthe benefits generated by education for both individuals and society among other factors that justify theinvestment of public resources. Reasons that justify publicintervention on education are analyzed. Results show thatgovernments basically use public financing to satisfy theneed of resources, moving from a bureaucratic model ofresources distribution to a market model where the governmentbecomes a consumer of educational services thathave been chosen by individuals themselves.